Bridget Jones's diary [videorecording (DVD)] - Maguire, Sharon; Zellweger, Renée, 1969-; Firth, Colin, 1960-; Grant, Hugh; Broadbent, Jim; Jones, Gemma; Fielding, Helen, 1958- (Miramax Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2004)
In her mid-thirties, still single and still being set up with dates by her mom, Bridget decides she needs to make a change in her life. She falls for her boss who uses her and then dumps her. In the meantime, Bridget keeps running into the divorced guy her mom tried to set her up with, and he happens to be ex-friends with her boss. She uses her diary as a confessional and she begins to wonder if she will ever find true love.